The cardiovascular system at a glance - Aaronson, Philip I. (Philip Irving), 1953-; Ward, Jeremy P. T.; Connolly, Michelle J. (Hoboken, NJ : Wiley-Blackwell, 2020)
'This concise and accessible text provides an integrated overview cardiovascular medicine - considering the basic sciences which underpin the cardiovascular system and applying this knowledge to clinical practice and therapeutics. Highly visual colour illustrations complement the text and consolidate learning. The Cardiovascular System at a Glance is the perfect introduction and revision aid to understanding the heart and circulation and now also features: New chapters on stroke and examination/imaging Expanded chapters on heart block and ECGs Enhanced artwork programme Brand new and updated clinical case studies and multiple-choice questions online The fifth edition of The Cardiovascular System at a Glance is an ideal resource for medical students, whilst students of other health professions and specialist cardiology nurses will also find it invaluable'--
Includes index.
Keywords: Cardiovascular System -- anatomy & histology; Cardiovascular Diseases; Cardiovascular Physiological Phenomena; Handbook